Education with Ecological Roots - José Alberto Rubí-Barquero (Revista Electronic@ Educare, 2012)
This paper explains how modernity develops its own form of education to achieve its objective of conquering nature, and the related environmental consequences.  In this context, this paper proposes a new education nurtured from ecological knowledge, leaving behind the fragmentary and mechanic mission of the world –a characteristic of modernity– to promote an alternative awareness focused on a new way of relationships with our natural environment and other individuals.